Innovative History Learning through Virtual Field Trips Model - Moh. Imron Rosidi; Disman; Kokom Komalasari; Erlina Wiyanarti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
The purpose of this research is to create an innovative history learning model by using a virtual field trip model. The problem will be studied in this study are: (1) what is the essence reality in learning history? (2) how is the application of the virtual field trip model to a history learning? Research method selected for this study is a literature study where the data material needed are obtained from books, journals, encyclopedias, articles and others. According to the study result, it defines a learning history is a teaching and learning activity regarding past events with conveyed meaning for the present. Within its development process in responding to the Covid 19 pandemic, an innovative virtual field trip model was created and designed to make students able to play an active role in the history learning process which can be seen from the following syntax: (1) Determining the learning materials, (2) Guiding the group/individual investigations, (3) Presenting the result of students’ investigation and (4) Evaluation. Keywords:  Learning Model, History Learning, Virtual Field Trips